The role of ai in supporting english language learning in technical and vocational education - Khor, Melissa Suan Chin; Che’ Lah, Che’ Fadhilah (GADING Journal for the Social Sciences, 2025)
This study examined the role of Artificial Intelligence (AI) tools in supporting English language learning among students at Politeknik Kota Bharu, a Technical and Vocational Education and Training (TVET) institution in Malaysia. The objective was to determine how AI contributes to learning and which aspects of proficiency benefit most. A cross-sectional survey was conducted with 344 students from four departments, who had prior exposure to AI tools. Data were collected using a 13-item questionnaire covering exercises, assignments, and presentations. The instrument was reviewed by experts, piloted, and validated through factor analysis, with subscale reliabilities ranging from .88 to .91. Items were rated on a five-point Likert scale. Descriptive analysis shows that assignments yielded the highest benefit (M = 4.00, 95% CI [3.91, 4.09]), followed by exercises (M = 3.94, 95% CI [3.85, 4.03]) and presentations (M = 3.94, 95% CI [3.86, 4.02]). Inferential tests indicated that Semester 1 students reported greater grammar support in exercises (F (2, 341) = 4.26, p < .05, η² = .04), while female students perceived stronger pronunciation support in presentations (t (342) = 2.03, p < .05, d = 0.22). A repeated-measures ANOVA confirmed that assignments were rated higher than the other domains (p < .05, d ≈ 0.28). The findings suggest that AI tools complement English instruction in TVET, particularly in writing tasks, while also aiding comprehension and oral communication. As a single-site, self-report study, generalisation remains limited, underscoring the need for further research across institutions.